Blockchain technology in supply chains – improving end-to-end business performance - Cees J. Gelderman; Janjaap Semeijn; Niels Smit (The Central European Review of Economics and Management (CEREM), 2022)
Aim: Blockchain technology (BCT) is a relatively new technological development, promising strong gains in the areas of product traceability and visibility, end-to-end coordination (E2E), governance, and efficiency of supply chains. The aim of this study is to gain a better understanding of the impact of BCT on these performance measures. Design / Research methods: Hypotheses were tested with survey data from 119 supply chain professionals from Northern American SMEs. Conclusions / findings: The results confirm the positive impacts of BCT on all performance measures. E2E coordination is the integration of information, goods, and money within an organisation or supply chain. E2E coordination appeared to benefit from the use of BCT, enabling information sharing in a safe way. The findings suggest that BCT use fosters E2E coordination, which in its turn also positively affects financial performance. Originality / value of the article: Despite the increasing interest in and use of, BCT, there is little empirical evidence for the effect on supply chain performance. Many studies are anecdotal and lack empirical evidence. Implications of the research (if applicable): Companies should acknowledge the impact of BCT use on the various supply chain performance measures. Implementing and using BCT is likely to foster improvement in a wide range of performance indicators. Limitations of the research (if applicable): Companies use different types, versions, varieties, and forks of blockchain, all having their own strong and weak points. Future studies could investigate and include the nuances within different forks of BCT.
Keywords: M1; 330; Blockchain technology; product traceability; operational efficiency